1984
DOI: 10.1200/jco.1984.2.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of carminomycin versus 4'-epidoxorubicin in advanced breast cancer.

Abstract: Sixty-three evaluable patients with advanced breast cancer were randomly allocated to receive three-week intravenous courses of carminomycin (18 mg/m2) or 4'-epidoxorubicin (90 mg/m2). The former yielded one (3%) partial response for nine weeks among 29 patients whereas, in the other arm, nine (27%) of 34 patients achieved partial response for a median of 28 weeks (range, nine to 36 weeks; p less than 0.02). The major toxic effect of these anthracyclines was leukopenia with median white blood cell nadirs of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Seven early phase I1 trials all used the 3-weekly schedule (154,(219)(220)(221)(222)(223)(224). The average response rate in 147 patients is 25%, but these trials were all very small, recruiting from 13-36 patients with response rates ranging from 6% to 43%.…”
Section: Advanced Breast Cancer Phase II Trialsmentioning
confidence: 99%
“…Seven early phase I1 trials all used the 3-weekly schedule (154,(219)(220)(221)(222)(223)(224). The average response rate in 147 patients is 25%, but these trials were all very small, recruiting from 13-36 patients with response rates ranging from 6% to 43%.…”
Section: Advanced Breast Cancer Phase II Trialsmentioning
confidence: 99%
“…Subsequently clear evidence emerged that not all anthracyclines had equal efficacy in metastatic breast cancer. For example idarubicin, esorubicin and carcinomycin had inferior response rates to doxorubicin and/or epirubicin (Rozencweig et al, 1984;Bonfante et al, 1986;Lopez et al, 1989). However, in vitro studies indicate that daunorubicin has equivalent cytotoxicity to doxorubicin in breast adenocarcinoma lines (Wiles et al, 1997).…”
mentioning
confidence: 99%
“…At the time this study started, clinical experience suggested that doxorubicin 75 mg m-2 and epirubicin 90 mg m-would induce similar degrees of myelotoxicity (Rozencweig et al, 1984;Bonfante et al, 1982). In 1990, Mouridsen reviewed 10 years of clinical experience with epirubicin and calculated the equitoxic dose ratio for the haematological toxicity of doxorubicin and epirubicin to be 1:1.2 (Mouridsen et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…similar anti-tumour activity but less toxicity (Casazza et al, 1980;Schrauer et al, 1981;Bonfante et al, 1982;Young and Weenen, 1984). In the early phase II studies in metastatic breast cancer, epirubicin showed anti-tumour activity similar to that of doxorubicin (Rozencweig et al, 1984). The toxicities encountered with epirubicin therapy were: leucopenia, nausea and vomiting and no severe life-threatening cardiac toxicity up to a cumulative dose of about 1000 mg m-2.…”
mentioning
confidence: 97%
See 1 more Smart Citation